ANALISIS PERENCANAAN DAN PENGANGGARAN UNTUK ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA BADAN KEUANGAN KABUPATEN KEPULAUAN SANGIHE TAHUN ANGGARAN 2015 - Barbakem, Dealice Ivana; Tinangon, Jantje J.; Sabijono, Harijanto (Universitas Sam Ratulangi, 2018)
Planning and budgeting is a part which cannot be seperated from the proccess of government financial management. Need for integrity against a schedule of planning and budgeting Anggaran Pendapatan dan Belanja Daerah (APBD), linkages planning document that one against the other, as well as effective and efficient local government solutions to constrains in the planning and budgeting of the previous fiscal year APBD to be implemented in the next fiscal year. Badan Keuangan Kabupaten Kepulauan Sangihe is a functional government part that has the task of carrying out the affairs of local governance best on the principle of autonomy and helper task in the areas of income, asset and financial management areas, so that the operations of the system of government financial arrangements in particular regions can be run well. The purpose of this research was to determine whether the proccess of planning and budgeting for Anggaran Pendapatan dan Belanja Daerah (APBD) on Badan Keuangan Kabupaten Sangihe fiscal year 2015 is in compliance with Permendagri Nomor 13 Tahun 2006.This research uses descriptive research method. The research results showed of 14 steps, 1 of which shows the time and discrepancy functions according to Permendagri Nomor 13 Tahun 2006.Â Â Â Keywords : Planning, Budgeting, Regional Expenditure